Study of association between urine albumin creatinine ratio and ankle brachial index or peripheral arterial disease in type 2 diabetes mellitus patients - Saxena, Puneet; Chadha, Deepak; Goyal, Rishika; Shanbogh, Adarsh Kenchappa (International Journal of Advances in Medicine, 2020)
Background: To establish association between urine albumin creatinine ratio and ankle brachial index or peripheral arterial disease in type 2 diabetes patients. Methods: Total 74 patients of type 2 diabetes mellitus of >50 years of age subjected to calculation of urine albumin creatinine ratio and ankle brachial index was calculated using doppler sonography and estimation of peripheral arterial diseases was done. The data obtained subjected to analysis. Results: In group with ABI <0.9 suggestive of PAD, mean age of the patient was 62.32±5.8 years, mean BMI was 26.11±2.48kg/m2, mean duration of diabetes was 11.19±41 years, 7 (18.92%) were smokers, 15 (40.54%) were insulin users, 27 (72.97%) were hypertensive, mean SBP was 142.49±13.46mmHg, mean DBP was 84±6.42mmHg, mean serum cholesterol was 221.35±17.10mg/dl, mean serum triglyceride was 242.81 ± 17.10mg/dl, mean serum HDL was 44.03±5.77mg/dl, mean serum LDL was 116.89±28.77mg/dl, mean urine ACR was 294.62±314.90mg/gm, prevalence of normoalbuminuria, microlbuminuria and macroalbuminuria was 12 (32.43%), 21 (56.76%) and 4 (10.81%) respectively. The statistical significant difference was found in age, duration of diabetes, number of patients on insulin therapy, systolic BP, serum cholesterol, triglyceride, LDL, HDL, urine ACR and distribution of albuminuria. Conclusions: we conclude that statistical significant relationship exist between urine ACR and PAD. Hence urinary ACR can be considered as surrogate marker for early prediction of PAD in elderly patients with type 2diabetes mellitus eventually leading to aggressive intervention for prevention and management.